Chemical and Functional Characteristics of Modified Flour from Durians Seeds - Muhammad Azmi Alzuhri; Setyohadi Setyohadi; Ridwansyah Ridwansyah (Jurnal Rekayasa Pangan dan Pertanian, 2015)
The research was aimed to find the effect of yeast on the quality of modified flour from durians seeds. The research had been performed using a completely randomized design with two factors namely kind of yeast J1 = yeast of tape, J2 = yeast of tempeh, J3 = combination of yeast of tape dan yeast of tempeh and yeast concentration : K1 = 0 %, K2 = 0,2%, K3 = 0,4%, K4 = 0,6%. Parameters analyzed were water content, ash content, fat content, fiber content, protein content, water and oil absorption,acidity degree and baking expansion. The results showed that the kind of yeast had highly significant effect on water content, acidity degree and had significant effect on ash content. Concentration of yeast had highly significant effect on water content, ash content, fat content, fiber content, protein content, water and oil absorptio, acidity degree, starch content and baking expansion. Interaction of the two factors had highly significant effect on acidity degree and baking expansion. Yeast of tape and concentration of 0,6% yeast gave the best quality characteristic of modified flour from durians seeds. Keywords: Durians seeds, modified flour yeast